Human Resource and Skill Requirements In the Gems and Jewellery Industry.: - (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The Indian gems and jewellery industry has animportant position in the Indian economy due to its large-scale exportpotential. Breaking the shackles of being an ethnic and conventional industry,it has set growth standards of 15-20% in the past couple of years. The boom ofthis industry is essentially driven by the impressive export performance.Today, this sector is country’s second highest foreign exchange earner (aftertextile industry) and it contributes about one fifth of country’s export. TheIndian Gems and Jewellery Export Promotion Council (GJEPC) has reported thatIndian gems and jewellry sector has surpassed its export target of $16 billionin 2007, two years in advance.  Export in2005-06 rose to $16.67 billion, a growth of more than 6%. According to GJEPC,the sector is likely to grow at 20-25% in 2006-07. The growth was primarilydriven by the cut and polished diamond segment, which registered growth of morethan 6% in 2005-06. India is the largest manufacturer of cut and polisheddiamonds in the World. It is estimated that 11 out of 12 finished diamonds arefrom Surat in India.